Clinical Dilemmas in Inflammatory Bowel Disease. - Irving, Peter (John Wiley & Sons, 2007)
Evidence-based guidance to answer more than 60 controversial clinical questions on inflammatory bowel disease. Clinical Dilemmas in Inflammatory Bowel Disease is a practical handbook providing quick but detailed answers to the questions and challenges that you are faced with daily in the clinical setting. Each short chapter addresses a different topic and provides evidence-based guidance on subjects ranging from optimising current management through to special management problems and novel treatments. This book is suitable for all medical professionals involved in the care of patients with IBD.